KELAYAKAN FINANSIAL USAHA PETERNAKAN AYAM PETELUR DI KECAMATAN SIGI BIROMARU KABUPATEN SIGI (STUDI KASUS CV. BELONA MANDIRI) - Handayani, Sayekti; Maksum, Haerani (FAPETKAN UNTAD, 2011)
The study aimed to determine the financial feasibility of laying hens business of CV. Belona Mandiri in Kecamatan Sigi Biromaru Kabupaten Sigi. The research was carried out on 27 July to 24 August 2009 in Kecamatan Sigi Biromaru Kabupaten Sigi. The research used a Case Study method. The commercial layer financial data was collected through the bookkeeping of CV. Belona Mandiri since the commencement of the business. Data processed using the investment criteria such as NVP, the Net B/C and IRR. The research results showed that the Net B/C was 1.32% with the NPV of IDR 1,566,751,355 at interest rates of 16% and IDR 1,495,487,599 at interest rate of 18% while the IRR was 75.96%. This indicated that the layer business of CV. Belona Mandiri is financially feasible. Key Words: Financial analysis, layer poultry.